« Un-American ». Usages et appropriations politiques d’une catégorie contradictoire (1886-1916) - Jean-Louis Marin-Lamellet (Transatlantica)
This article analyzes the relationship between radicalism and nationalism by focusing on the word un-American. Although the term is ubiquitous in American political discourse, there has been hitherto no systematic analysis of the concept. This paper investigates the political uses and appropriations of a contradictory category in print culture from 1886 to 1916. As a new capitalist order was emerging and labor conflicts were intensifying, un-American was not yet the exclusive territory of conservatives. Both radicals and their opponents were vying to appropriate the term and thereby the legacy of the Founding Fathers. Right-wing groups used un-American to excommunicate radicals while left-wing activists used it to foster a patriotic tradition of dissent. These two aspects will be examined though the political analysis of controversies over the meaning of social protest practices and their repression. The article will conclude by considering the role of World War One in imposing the antiradical interpretation of un-American.